THE DETERMINATION OF MICROORGANISMS IN INDOOR AND OUTDOOR ATMOSPHERE IN THE Y.T.U. DAVUTPASA CAMPUS - Baysal, Feysa; Adar, Elanur; Sakar, Suleyman; Nuhoglu, Yasar (YILDIZ TECHNICAL UNIV, 2019)
Air can contain a number of foreign matters and microorganisms in various sizes, which may be harmful to human health besides essential substances necessary for respiration such as oxygen. The air quality in terms of microbiology in indoor and outdoor environments plays an important role in determining the possible risks and the precautions to be taken. The aim of this study is to examine the microorganisms in indoor and outdoor air in the Davutpasa campus of Yildiz Technical University. The active and passive sampling methods were used in nine different indoor and outdoor atmospheric environments. The best results were obtained by active sampling and membrane filtration methods. In the samples taken in March, the highest bacterial colony was detected in the wastewater laboratory at 35 degrees C. The highest bacterial and fungal colonies were found in the wastewater laboratory and in the middle garden, respectively. In the samples taken in April, the highest the number of bacteria at 20 degrees C was in the microbiology laboratory while the number of fungi showed differences according to the type of cultivation methods. In the gram staining, gram positive bacteria belonging to Sarcina sp, gram negative Monococcus sp., gram positive Diplococcus sp., gram positive Tetracoccus sp., gram-negative actinomycetes (branched bacteria), gram-negative Vibrio sp. and miscellaneous fungi have been observed. As a result, it has observed that there are various bacteria and fungi in the indoor and outdoor air we breathe. The number of microorganisms has changed according to the environment conditions.
Keywords: Microorganisms; indoor; outdoor; atmosphere; STONE MONUMENTS; AIR-POLLUTION; PREVALENCE; DWELLINGS; ERZURUM; Engineering